A house of words : Jewish writing, identity, and memory - Ravvin, Norman (McGills-Queen's studies in ethnic history ; Series two, 1997)
Arguing that Jewish North American writing is too commonly discussed as part of the mainstream, neglecting the Jewish aspects of the works, Ravvin places the writing of Bellow, Richler, Cohen, West, Mandel, Roth, and Rosenfarb within the Jewish context that the works demand. Ravvin depicts a Jewish cultural landscape within which postwar writers contend with community and identity, continuity and loss, and highlights the way this particular landscape is entangled with broader literary and cultural traditions. He considers Bellow and West alongside apocalyptic narratives, discusses Cohen in relation to the counterculture, examines Mandel's postmodern view of history, and looks at autobiography and ethics in Roth and Rosenfarb. At once scholarly and poetic, A House of Words will appeal to the general reader of Canadian, American, and Jewish literature and history, as well as to specialists in these fields.